Axonal and Dendritic Morphology of Excitatory Neurons in Layer 2/3 Mouse Barrel Cortex Imaged Through Whole-Brain Two-Photon Tomography and Registered to a Digital Brain Atlas - Liu, Yanqi; Foustoukos, Georgios; Crochet, Sylvain; Petersen, Carl C.H. (Frontiers in Neuroanatomy, 2022)
Communication between cortical areas contributes importantly to sensory perception and cognition. On the millisecond time-scale, information is signaled from one brain area to another by action potentials propagating across long-range axonal arborizations. Here, we develop and test methodology for imaging and annotating the brain-wide axonal arborizations of individual excitatory layer 2/3 neurons in mouse barrel cortex through single-cell electroporation and two-photon serial section tomography followed by registration to a digital brain atlas. Each neuron had extensive local axon within the barrel cortex. In addition, individual neurons innervated subsets of: secondary somatosensory cortex; primary somatosensory cortex for upper limb, trunk and lower limb; primary and secondary motor cortex; visual and auditory cortical regions; dorsolateral striatum; and various fiber bundles. In the future, it will be important to assess if the diversity of axonal projections across individual layer 2/3 mouse barrel cortex neurons is accompanied by functional differences in their activity patterns.